Використання zero knowledge proof для захисту персональних даних під час ідентифікації особи - Хотян, М. О.; Побіженко, І. О. (ХНУРЕ, 2025)
This work focuses on the application of Zero Knowledge (ZK) protocols to enhance the securІТy and privacy of user authentication and personal data verification. ІТ explores how ZK proofs can be used to authenticate users wІТhout revealing sensІТive personal information, such as passwords, and examines the potential of ZK protocols in verifying the validІТy of personal data while preserving privacy. The paper discusses various cryptographic methods, including Groth16 and PLONK, and highlights the advantages of using these protocols to prevent unauthorized access and reduce the risk of data leaks.
Keywords: zero knowledge proof; захист персональних даних; ідентифікація особи